Hilmi Ziya’s article about kyrgyzs in Оttoman language (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The history of the Kyrgyz can be found in articles and records published in periodicals, as well as archival documents of the Ottoman state. Among these is Hilmi Zia’s article about the Kyrgyz6 written in ottoman Turkish on January 1, 1924. Despite its shortcomings, the work may be considered an adequate scholarly contribution in informing the newly founded Turkish Republic about the Kyrgyz people’s history. The article is crafted on European research materials and historical sourses.
Keywords: Hilmi Ziya, Ottoman press, article, Kyrgyz, Kyrgyz history, Ottoman language